Surface analysis of Pd/ZnO catalysts dispersed on micro-channeled Al-foils by XPS - Dumbuya, K.; Denecke, Reinhard; Steinrück, Hans-Peter (Applied Catalysis A-General, 2008)
We have investigated the surface composition of Pd/ZnO catalysts dispersed on micro-channeled Al-foils in a non-activated and in the activated state, between 300 and 700 K using X-ray photoelectron spectroscopy (XPS). While the surface of the non-activated catalyst, as obtained after calcination, is composed of PdO, the surface of the activated (reduced) catalyst consists of predominantly PdZn and ∼30% metallic Pd. When increasing the temperature up to 700 K in UHV significant structural surface changes were observed for both samples. For the non-activated sample, PdO was reduced mainly to the Pd metal with some fraction of PdZn alloy. For the activated catalyst, the fraction of metallic Pd was also converted to PdZn, yielding a pure alloy, which is stable to at least 600 K. At 700 K both samples show changes due to segregation of Mg from the micro-channeled Al-foils onto which the powdered catalysts were deposited, which contains 3% Mg. © 2008 Elsevier B.V. All rights reserved.